Distribution patterns of micronektonic crustaceans (Decapoda, Euphausiacea, and Lophogastrida) in the tropical and subtropical Atlantic Ocean - Díaz Pérez, Javier; Landeira, Jose M.; Hernandez-Leon, Santiago; Reyes-Martinez, M. Jose; Gonzalez-Gordillo, Juan Ignacio (Progress in Oceanography, 2024)
Large pelagic crustaceans are a main component of the micronekton community in the deep-sea having an important role in the food webs and the biological carbon pump. However, they are scarcely studied in comparison to other groups such as mesopelagic fish. Here, we analyse day/night and bathymetric variability in taxonomic composition, abundance, and biomass across a latitudinal transect in the Atlantic Ocean from off Brazil (15 degrees S) degrees S) to the Canary Islands (25 degrees N). degrees N). A total of 95 species were identified belonging to 9 different families, of which Euphausiidae was the most abundant family and Acanthephyridae the family contributing the most to the total biomass. We found distinct assemblages associated with Atlantic ecoregions related to the environmental variables. Diel vertical migrations were detected along the entire transect, even crossing the oxygen minimum zone, likely due to the metabolic adaptations of these organisms. 12 1,298 4,1 Q1 Q1 SCIE 11,0